Identifying risk factors for postpartum depression in Mashhad, Iran, 2017–2024: a population-based case-control study - Amin Moradi; Mehdi Norouzi; Ehsan Mosa Farkhani (Archives of Public Health)
Abstract Background Postpartum depression (PPD) is a common and debilitating disorder affecting mothers worldwide. This study aimed to identify risk factors and the frequency of PPD in Mashhad, Iran. Methods A population-based case-control study was conducted using data from the Sina Health Information System (SINAEHR) from March 1, 2017, to June 20, 2024. The Edinburgh Postpartum Depression Scale was used to identify cases (score > 12) and controls (score ≤ 12). Bivariate and multivariate logistic regression analyses were performed to determine risk factors associated with PPD. Results Among 108,952 women evaluated, 3,407 (3.03%) were diagnosed with PPD and matched with an equal number of controls. Significant risk factors for PPD included maternal age ≤ 20 years (OR = 1.76, 95% CI: 1.31–2.36), history of abortion (OR = 1.25, 95% CI: 1.15–1.42), cesarean delivery (OR = 1.22, 95% CI: 1.11–1.34), preterm delivery (OR = 1.99, 95% CI: 1.67–2.37), twin births (OR = 2.10, 95% CI: 1.41–3.24), and drug use (OR = 5.76, 95% CI: 2.90–11.33). Psychological factors were strongly associated with PPD, including history of anxiety (OR = 2.48, 95% CI: 2.06–2.93), domestic violence (OR = 4.08, 95% CI: 2.43–6.59), history of depression (OR = 5.31, 95% CI: 4.58–6.61), and psychological distress (OR = 4.94, 95% CI: 3.91–6.23). Conclusion This study identified multiple risk factors for PPD, with psychological factors showing the strongest associations. These findings highlight the importance of screening for mental health issues and providing targeted support to high-risk women during pregnancy and the postpartum period to prevent and manage PPD effectively.